“They wanted to, but they just couldn’t get there”: GBA + implementation and gaps during the COVID-19 pandemic in Canada - Muhammad Haaris Tiwana; Lara Hollmann; Julia Smith (International Journal for Equity in Health)
Abstract Purpose To improve understanding of the barriers and enablers to implementing gender and intersectional analysis during the COVID-19 pandemic in Canada. Methods We conducted a policy document analysis (n = 70) of equity-focused policies of the Canadian government published between March 2020 and August 2023. This analysis was complemented with 16 semi-structured key informant interviews with federal policy actors and leadership of civil society organizations. Results Pandemic policy documents demonstrated multiple commitments to address pandemic related inequities, with key informants describing collaborative approaches to implementing these policies, but also limits in terms of the urgent and diffused nature of pandemic response. Implementation gaps related to accessible information, health services and vaccinations were noted and attributed to a reliance on civil society actors who lacked sufficient and sustainable resources, and the behaviors of priority populations whose capacity to comply was limited by the same inequities the policies sought to address. Conclusion The Canadian federal government made concerted efforts to address the needs of a range of priority populations and equity issue areas within its pandemic response, with mixed results. Having a pre-established framework to guide implementation and related relationships overcame some of the urgency challenges related with pandemic response. However, implementation gaps reflected preexisting inequities shaped by broader economic, social and political systems which were infrequently addressed in pandemic policies. There is a need for greater understanding of policy implementation gaps during emergency and crisis response.